Psicose apropriado: deslocamento e transformações de uma imagem no cinema pelo video - Alexandre de Souza Milagres (2009)
This investiges the films appropriations that are made by video, in works: 24 Hours Psycho (1993), by Douglas Gordon, Uncopyrighted Schizo (2004), by Diego Lama and Psycho (s): The Live Remix (2006), by IP Yuk-Yiu. In all this three videos is identified the same image, taked as reference in their appropriations: the image of the movie Psycho (1960), of Alfred Hitchcock, and two of three videos have also images by his remake, the Psycho (1998), of Gus Van Sant. The approach we do about the relation of this three video is made to understand the way how each video appropriate the cinema, as well as the type of image they create when transform the images from the Psycho movie. Using the reflections of Arthur C. Danto (2006), Hans Belting (2006), Nicolas Bourriuad (2007) and Philippe Dubois (2004), we construct in this dissertation a profile of the types of appropriation that occurs in the general context of contemporary art, and specifically the films appropriations made by video, that helps to understand the appropriations made by Gordon, Yuk-Yiu and Lamas videos. In the end, we taking up the ideas of moving-image and time-image in Deleuze, tracing through its grounds what we consider to be the image that these videos create when appropriate the Psycho film.